2010
DOI: 10.1677/joe-10-0352
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of hyperglycemia in diabetic rats by intraportal injection of insulin-producing cells generated from surgically resected human pancreatic tissue

Abstract: Although islet transplantation holds promise for the treatment of diabetes, the scarcity of donor tissue remains a major drawback. The aim of this study is to generate insulinproducing cells from adult human pancreatic cells isolated from surgically resected pancreatic tissue. To isolate pancreatic endocrine precursor cells from 57 surgically resected pancreases, the cells were cultured and propagated in conditioned medium after which they were differentiated in Matrigel. The resultant cells were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Moreover, 9/19 mice transplanted with progenitor cells, and 2/4 mice transplanted with IPCs, secreted C-peptide in response to glucose (Zang et al, 2010). Allotransplantation of IPCs differentiated from islet progenitor cells produced similar results (Shyu et al 2011). In this study, progenitor cells cultured in matrigel differentiated into IPCs following transplantation into diabetic mice.…”
Section: Transplantation Of Differentiated Stem Cellssupporting
confidence: 59%
See 2 more Smart Citations
“…Moreover, 9/19 mice transplanted with progenitor cells, and 2/4 mice transplanted with IPCs, secreted C-peptide in response to glucose (Zang et al, 2010). Allotransplantation of IPCs differentiated from islet progenitor cells produced similar results (Shyu et al 2011). In this study, progenitor cells cultured in matrigel differentiated into IPCs following transplantation into diabetic mice.…”
Section: Transplantation Of Differentiated Stem Cellssupporting
confidence: 59%
“…Other studies report the successful use of transgenesis to differentiate MSCs into IPCs, or upregulation of genes (mainly PDX-1 or betacellulin) related to signalling pathways that trigger this process (Karnieli et al, 2007;Li et al, 2007;Li et al, 2008;Hisanaga et al, 2008;Limbert and Seufert., 2009;Yuan et al, 2010;Paz et al, 2011). Moreover, coating the tissue culture flasks with substrates such as fibronectin or laminin can also induce MSCs to differentiate into IPCS (Moriscot et al, 2005;Chang et al, 2008;Lin et al, 2010;Lin et al, 2011).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, new therapeutic strategies have been studied in diabetes management. Shyu et al, [38] described the isolation of pancreatic endocrine precursor cells, from adult human pancreatic tissue, and the redifferentiation of insulin-secreting β-like cells from in vitro-cultured insulin-producing cell precursors. These data emphasize that surgically resected pancreatic tissue may represent an alternative source of functional insulin-producing cells and to minimize the cardiovascular dysfunctions of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the amount of insulin produced by these cells was much lower than what is produced by a naturally occurring islet-derived β-cell. It has also been shown that endocrine precursors can be derived from surgically resected portions of human pancreas and that islets themselves contain a population of mesenchymal stem cells [41,42]. Recently published data bolsters the idea of a precursor cell in pancreas citing the existence of insulin positive multipotent stem cells that give rise to pancreatic and neural lineages and that ameliorate diabetes in animal models [43].…”
Section: Discussionmentioning
confidence: 99%